Bolus versus Continuous Feeding to Optimize Anabolism in Neonates - Davis, Teresa A. (Curr Opin Clin Nutr Metab Care, 2015)
PURPOSE OF REVIEW: Neonates with feeding difficulties can be fed by orogastric tube, using either continuous or bolus delivery. This review reports on recent findings that bolus is advantageous compared to continuous feeding in supporting optimal protein anabolism. RECENT FINDINGS: Whether bolus or continuous feeding is more beneficial has been controversial, largely due to limitations inherent in clinical studies such as the presence of confounding variables and the inability to use invasive approaches. Recent studies using the piglet as a model of the human neonate showed that, compared to continuous feeding, bolus feeding enhances protein synthesis and promotes greater protein deposition. The increase in protein synthesis occurs in muscles of varying fiber type and in visceral tissues whereas muscle protein degradation is largely insensitive to feeding pattern. This higher protein synthesis rate is enabled by the rapid and profound increases in circulating amino acids and insulin that occur following a bolus feed, which activate the intracellular signaling pathways leading to mRNA translation. SUMMARY: Recent findings indicate that bolus feeding enhances protein synthesis more than continuous feeding, and promotes greater protein anabolism. The difference in response is attributable to the pulsatile pattern of amino acid- and insulin-induced translation initiation induced only by bolus feeding.